2017
DOI: 10.1159/000455162
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Obesity on Outcomes of Percutaneous Nephrolithotomy in Renal Stone Management: A Systematic Review and Meta-Analysis

Abstract: length of hospital stay after treatment existed between super-obese and normal-weight individuals (95% CI -0.15 to 0.37, p = 0.39). Additionally, no obvious differences in terms of operation time existed between obese and normal-weight individuals (95% CI -3.36 to 1.17, p = 0.34). However, the operation time was longer among super-obese individuals than among normal-weight individuals (95% CI -22.64 to -1.40, p = 0.03), and the length of hospital stay was shorter among obese patients than among normal-weight p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 29 publications
4
34
0
1
Order By: Relevance
“…However, BMI was associated with increased blood transfusion rate. These findings agree with Zhou X et al [20] who demonstrated that PCNL in obese and morbidly obese patients yields a stone-free rate that is comparable to that achieved in nonobese one. Contrary to our finding, Ş imşek A et al [21] reported that BMI does not affect the blood transfusion rate in PCNL.…”
Section: Discussionsupporting
confidence: 92%
“…However, BMI was associated with increased blood transfusion rate. These findings agree with Zhou X et al [20] who demonstrated that PCNL in obese and morbidly obese patients yields a stone-free rate that is comparable to that achieved in nonobese one. Contrary to our finding, Ş imşek A et al [21] reported that BMI does not affect the blood transfusion rate in PCNL.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, the use of F-URS in obese patients presents challenges including long-term stone discharge, increased overall cost and requirement of multiple interventions (Sari et al, 2013). However, traditional PCNL has been proven to be a safe and effective alternative in obese patients (Trudeau et al, 2016;Zhou et al, 2017). When compared with conventional PCNL, super-mini percutaneous nephrolithotomy (SMP) causes less blood loss and fewer perioperative complications (Zeng et al, 2016;Liu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the use of F-URS in obese patients presents challenges including long-term stone discharge, increased overall cost and requirement of multiple interventions [7]. However, traditional PCNL has been proven to be a safe and effective alternative in obese patients [8][9]. When compared with conventional PCNL, super-mini percutaneous nephrolithotomy (SMP) causes less blood loss and fewer perioperative complications [10][11].…”
Section: Introductionmentioning
confidence: 99%